6(c-6)=5(2+c)

Simple and best practice solution for 6(c-6)=5(2+c) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(c-6)=5(2+c) equation:


Simplifying
6(c + -6) = 5(2 + c)

Reorder the terms:
6(-6 + c) = 5(2 + c)
(-6 * 6 + c * 6) = 5(2 + c)
(-36 + 6c) = 5(2 + c)
-36 + 6c = (2 * 5 + c * 5)
-36 + 6c = (10 + 5c)

Solving
-36 + 6c = 10 + 5c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-5c' to each side of the equation.
-36 + 6c + -5c = 10 + 5c + -5c

Combine like terms: 6c + -5c = 1c
-36 + 1c = 10 + 5c + -5c

Combine like terms: 5c + -5c = 0
-36 + 1c = 10 + 0
-36 + 1c = 10

Add '36' to each side of the equation.
-36 + 36 + 1c = 10 + 36

Combine like terms: -36 + 36 = 0
0 + 1c = 10 + 36
1c = 10 + 36

Combine like terms: 10 + 36 = 46
1c = 46

Divide each side by '1'.
c = 46

Simplifying
c = 46

See similar equations:

| 860=2(2x-65)+2x | | 3b^3-18b=10b-49 | | -x^2+17x-5=0 | | 0.05d-0.2-17=13 | | 8(t-4)-6(4t+3)=-17(t+5)+7 | | x^3+2x^2=150 | | 6x-6-4x=26+x | | 0.35x-1.2=0.2 | | -2=5(x+9)-8x | | 6t-0=5+8b | | 5(x+0.8)=16 | | -5=16t^2+70t+4 | | 2x^2+(3k-1)x+(3k^2-1)=0 | | -9(w-8)-(4w-1)=-14w | | v-8=16 | | lne-2x=8 | | 2x^2+(3k-1)x(3k^2-1)=0 | | [(x-105)/5] | | 7z+7-3z=9+3z+1 | | 0.8(x-0.1)=1.2 | | [(x-105)/4] | | 2x^2-3+2=0 | | p+6=x-y | | -5(y+5)=-4y-5 | | 41/45= | | 24/45= | | 0.9(x+2)-3=2(x+0.9)+4 | | 10x+(-3+6)=8 | | 31/45= | | 34/45= | | 6T-1=3(2T+5) | | (3x2)-(8/(-4))= |

Equations solver categories